The Battle for Standardised Cigarette Packaging in Europe Multi-Level Governance, Policy Transfer and the Integrated Strategy of the Global Tobacco Industry /: Multi-Level Governance, Policy Transfer and the Integrated Strategy of the Global Tobacco Industry. (2020) - Holden, Chris; Mackinder, Sophie
No abstract available